Open Quantum Systems An Introduction - e uthor; Huelga, Susana F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
In this volume the fundamental theory of open quantum systems is revised in the light of modern developments in the field. A unified approach to the quantum evolution of open systems is presented by merging concepts and methods traditionally employed by different communities, such as quantum optics, condensed matter, chemical physics and mathematical physics. The mathematical structure and the general properties of the dynamical maps underlying open system dynamics are explained in detail. The microscopic derivation of dynamical equations, including both Markovian and non-Markovian evolutions, is also discussed. Because of the step-by-step explanations, this work is a useful reference to novices in this field. However, experienced researches can also benefit from the presentation of recent results.
Introduction -- Mathematical tools -- Time evolution in closed quantum systems -- Time evolution in open quantum systems -- Quantum Markov process: mathematical structure -- Microscopic description: Markovian case -- Microscopic description: non-Markovian case -- Conclusion.
Keywords: Physics; Quantum theory; Mathematical physics; Physics; Quantum Physics; Numerical and Computational Physics; Mathematical Methods in Physics; Quantum Optics